THE ROLE OF SCHOOL AND CAREER GUIDANCE PROGRAMS IN DEVELOPING LEARNING MOTIVATION: A CASE STUDY OF AIN BEIDA, OUM EL BOUAGHI PROVINCE, ALGERIA - Guettali Abd El Ghani,; AS Lazhar, (International Journal of Innovative Technologies in Social Science, 2024)
Guidance approaches play a vital role in supporting learners and enhancing their motivation to learn. By offering academic guidance, career guidance, and mental health support, counselors can assist students in achieving their educational and career goals. Nurturing motivated learners is of utmost importance, as guidance programs can provide them with the necessary support and guidance to reach their full potential. Effective guidance programs involve individual assessments, tailored interventions, career training, and academic guidance. They also focus on diversity, individual needs, and interdisciplinary collaboration. Integrating technology, competency-based education, and projects can enhance the impact of guidance programs. Research shows positive long-term effects of guidance programs on academic performance, career readiness, and students' mental health. However, challenges such as limited resources and social stigma require attention from policymakers and educational institutions.